Circulating bacterial DNA and its taxonomic characterisation - Aarnio, Heidi (My University, 2025)
The role of human microbiome has been broadly investigated in disease and health. It has been shown that bacterial DNA circulate in the blood during various ailments. The presence of this circulating bacterial DNA (cbDNA) has been linked to onset and prognosis of various diseases. In addition to disease, cbDNA has been recently located from the blood of healthy individuals as a part of healthy blood microbiome (HBM). After the discovery of HBM, studies comparing the taxonomic composition of cbDNA between different patient populations and healthy volunteers have been conducted, showing the effect of cbDNA in multiple disease settings. This thesis is a precursory study to the role of cbDNA in systemic lupus erythematosus, a multiorgan rheumatic autoimmune disease with broad range of symptoms, focusing on characterising the taxonomy of HBM in different blood fractions; whole blood (WB), buffy coat (BC) and peripheral blood mononuclear cells (PBMCs). In this study DNA was extracted from blood samples, followed by 16S rRNA PCR and Illumina MiSeq sequencing. The data was processed in Galaxy using modified Mothur standard operating protocol. We found Actinobacteria to be the most common phylum in the PBMCs, BC and WB of healthy donors followed by Proteobacteria, Firmicutes and Bacteroidetes. We also found that different genera have preferential localisation within the blood fractions. The composition of bacteria phyla in the samples resembled skin microbiome. HBM was found to be diverse, dynamic, and individual. The methods used do however have some limitations and more research is needed.
Keywords: 16S rRNA PCR, cbDNA, Healthy blood microbiota